Combined Ionic Membrane and Silica Desiccant Configuration for Maintenance-Free Humidity Control in Equipment - Stavros Misopoulos; Dirk Nather; Jose Marques-Hueso (Applied Sciences, 2023)
Much scientific equipment requires the use of humidity control technologies. This includes instruments with hygroscopic optics, such as infrared spectrometers, OPOs and some lasers. The most common strategies include nitrogen purging or desiccant bag replacement, which involve maintenance and running costs. In this work we present a dual strategy, combining both ionic membranes and silica desiccant, which results in a reusable and maintenance-free scheme for humidity control. The desiccant action of the silica gels, the membrane, and combinations thereafter, are studied. It is shown that the combination of the silica gel desiccants and the membrane is the most efficient configuration, reducing the humidity from 73% to only 15% in 20 h in a 70 L volume and from 80% to 20% in 40 h in a 230 L volume. An experiment over 5 days showed that the status of the silica gel desiccants that had adsorbed high water vapor levels returned to normal after they were enclosed together with the ionic membrane in the 70 L volume. Finally, measurements taken by a commercial infrared spectrometer of the reduction in the H2O lines absorption in the mid-infrared region under the operation of the combined configuration are examined. It was demonstrated that H2O lines with low to moderate absorption almost disappeared when the humidity levels inside the spectrometer dropped from 42.5% to 15.1% in the span of 90 min, while lines with stronger absorption remained present even though they showed the highest percentage of change.